Building better performance through applied science: How NGBs and universities can work together - Callan, S.; Dieffenbach, K. (Olympic & Paralympic Coach, 2012)
Sport and the art of peak performance are an increasingly complex and high-stakes experiment that coaches and athletes pursue on a daily basis in the quest for Olympic gold. In their 2005 Olympic Coach article, "Downfall of sport science in the United States," Dr. Mike Stone and colleagues discussed the importance of integrating of the scientific approach with the art of coaching for the long-term, continued success of our sports programs. Unfortunately, this is not the approach taken by most programs, but not because of a lack of interest or value. The call for better integration and the systematic use of science in training is a tall order for coaches and National Governing Bodies (NGBs) to accomplish given the budget, personnel and time constraints that many programs face. A potential resource to help address these issues can potentially be found within institutions of higher learning. Throughout the U.S., academic programs abound that can assist sport programs in rising to meet the challenges of training and competing in the modern era of science-based training. NGBs and universities have the potential to form partnerships that are mutually beneficial in pursuit of these goals. Developing effective partnerships involves a variety of departments on college campuses collaborating with the NGBs. This article is designed to provide ideas for forming and fostering successful performance-focused partnerships and to initiate meaningful discussion between the groups.